Seismotectonic characterization of the Colombian Pacific region: identification of tectonic patterns through geostatistical analysis (2017)
Earthquake occurrence is a consequence of many processes within the Earth such as tectonic stress loading, fluid diffusion or static stress triggering. As a result of this, patterns of spatial and temporal distribution, that earthquakes have historically displayed, keep the footprint of the mechanisms that give them origin. Quantifying these patterns and the extent of the causality and correlation between seismic events is then an interesting and useful subject of study. It is useful because it opens the doors to more accurate estimations of the behavior of earthquakes, which inherently decreases the risk of catastrophes. The Colombian Pacific region is a zone that presents a high degree of geological complexity, it lies parallel to a trench where the Nazca plate subducts below the South American Plate, which inherently results in increased seismic activity and rupture. In this study a sequence of 134 events that happened in this zone in a period of 68 months is studied. These earthquakes are organized in complex spatial structures that were separated trough clustering analysis and then subjected to geostatistical analysis. The geostatistical analysis consisted of: an evaluation of the distribution of events as a function of time and a semivariogram analysis, by which the degree of correlation between events was studied. The interaction within these events is highly complex but, to some extent, some system wide correlations are observed. As opposed to what was initially expected, the semivariogram analysis did not manage to measure the degree of correlation for this particular sequence. What this means is that all semivariograms lie within a zone that denotes no-correlation and present a generalized uncorrelated form